Anti-TLR7 Antibody Protects Against Lupus Nephritis in NZBWF1 Mice by Targeting B Cells and Patrolling Monocytes - Murakami, Yusuke; Fukui, Ryutaro; Tanaka, Reika; Motoi, Yuji; Kanno, Atsuo; Sato, Ryota; Yamaguchi, Kiyoshi; Amano, Hirofumi; Furukawa, Yoichi; Suzuki, Hitoshi; Suzuki, Yusuke; Tamura, Naoto; et al. (Frontiers in Immunology, 2021)
Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by autoantibody production and multiple organ damage. Toll-like receptor 7 (TLR7), an innate immune RNA sensor expressed in monocytes/macrophages, dendritic cells (DCs), and B cells, promotes disease progression. However, little is known about the cellular mechanisms through which TLR7 drives lupus nephritis. Here, we show that the anti-mouse TLR7 mAb, but not anti-TLR9 mAb, protected lupus-prone NZBWF1 mice from nephritis. The anti-TLR7 mAb reduced IgG deposition in glomeruli by inhibiting the production of autoantibodies to the RNA-associated antigens. We found a disease-associated increase in Ly6Clow patrolling monocytes that expressed high levels of TLR7 and had upregulated expression of lupus-associated IL-10, CD115, CD31, and TNFSF15 in NZBWF1 mice. Anti-TLR7 mAb abolished this lupus-associated increase in patrolling monocytes in the circulation, spleen, and glomeruli. These results suggested that TLR7 drives autoantibody production and lupus-associated monocytosis in NZBWF1 mice and, that anti-TLR7 mAb is a promising therapeutic tool targeting B cells and monocytes/macrophages.